Does private income support sustainable agroforestry in Spanish dehesa? - Campos, Pablo; Ovando, Paola; Montero, Gregorio (Land Use Policy, 2008)
Oak woodland dehesa suffers from the aging of trees without a natural regeneration of young oaks coming in to replace them. Recent European Union (EU) policy reforms for rural development focus on supporting multifunctional agriculture that complies with the EU’s environmental goals, such as mitigating biodiversity losses and climate change. Such reforms could result in government support for natural woodland regeneration practices in European agroforestry systems, which are recognized for providing valuable environmental services. Managing dehesa cork oak and holm oak woodlands to stimulate the growth of new oaks could be an efficient option for maintaining, and even increasing, the dehesa’s current carbon stock and biodiversity. Here we develop and apply a new agroforestry accounting system based on the concept of Hicksian income to a dehesa in the Monfragu¨ e area of western Spain, using primary microeconomic data from a large case study. Private total income and profitability rates are measured for individual goods and services, and for the entire dehesa in a steady state. Our application extends the EU system of accounts for agriculture and forestry by including private amenity consumption by landowners and the gain or loss in human-made and natural capital. We compare an actual typical unsustainable woodland management scenario with an ideal sustainable management scenario in which there is a continuous regeneration and recruitment of holm and cork oaks as predicted by silvicultural models. The results show that, given current land use policy incentives, allowing a slow depletion of oak trees is more profitable for a dehesa private landowner than maintaining the dehesa’s trees. As a result many dehesa environmental services are gradually lost. This market failure requires new land use policies that induce private land owners to invest in the renewal of aging oak woodlands. To evaluate the impacts of this new policy, we show how private landowner income is affected when changes are made to achieve sustainable management of dehesa oaks. More research is needed in order to understand how the dehesa’s landowner market income and private amenities trade-off can affect the owner’s land use preferences and decisions.
Keywords: Amenities; environmental services; Monte; Oak silviculture; Rural development policy; Total income

Does private income support sustainable agroforestry in Spanish dehesa? (Land Use Policy, 2008)
Oak woodland dehesa suffers from the aging of trees without a natural regeneration of young oaks coming in to replace them. Recent European Union (EU) policy reforms for rural development focus on supporting multifunctional agriculture that complies with the EU’s environmental goals, such as mitigating biodiversity losses and climate change. Such reforms could result in government support for natural woodland regeneration practices in European agroforestry systems, which are recognized for providing valuable environmental services. Managing dehesa cork oak and holm oak woodlands to stimulate the growth of new oaks could be an efficient option for maintaining, and even increasing, the dehesa’s current carbon stock and biodiversity. Here we develop and apply a new agroforestry accounting system based on the concept of Hicksian income to a dehesa in the Monfragu¨ e area of western Spain, using primary microeconomic data from a large case study. Private total income and profitability rates are measured for individual goods and services, and for the entire dehesa in a steady state. Our application extends the EU system of accounts for agriculture and forestry by including private amenity consumption by landowners and the gain or loss in human-made and natural capital. We compare an actual typical unsustainable woodland management scenario with an ideal sustainable management scenario in which there is a continuous regeneration and recruitment of holm and cork oaks as predicted by silvicultural models. The results show that, given current land use policy incentives, allowing a slow depletion of oak trees is more profitable for a dehesa private landowner than maintaining the dehesa’s trees. As a result many dehesa environmental services are gradually lost. This market failure requires new land use policies that induce private land owners to invest in the renewal of aging oak woodlands. To evaluate the impacts of this new policy, we show how private landowner income is affected when changes are made to achieve sustainable management of dehesa oaks. More research is needed in order to understand how the dehesa’s landowner market income and private amenities trade-off can affect the owner’s land use preferences and decisions.